Arno Vogel, Marco Antonio da S. Mello e José Flávio P. de Barros. A galinha-d’Angola: iniciação e identidade na cultura afro-brasileira. Rio de Janeiro, Pallas/FLACSO; Niterói, EDUFF, 1993. 204p - Telles, Jocélio (Afro-Ásia, 1996)
.